A silicon-based composite negative electrode material and its preparation method and application

The prelithiation and high-quality coating of silicon oxide materials by in-situ coating-co-lithium sintering method solve the problem of prelithiation in the prior art that the coating and coating layers are uneven, and efficient electrochemical performance improvement is achieved.

CN116387491BActive Publication Date: 2025-03-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310463702.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-26
Publication Date
2025-03-18
Estimated Expiration
2043-04-26

AI Technical Summary

Technical Problem

The prior art destroys the original carbon cladding layer on the silicon oxide surface during prelithiation, resulting in attenuation of the cyclic performance of the material. The traditional cladding method results in uneven cladding and weak bonding force, affecting the material performance.

Method used

In-situ cladding-co-lithium sintering method is used to prelithiate the silicon oxide material and achieve high-quality cladding on the surface of the silicon oxide material. The ion conductor cladding layer is used as the shell to enhance the binding force between the prelithiated silicon oxide particles and the cladding layer.

Benefits of technology

It effectively reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, improves the first Coulomb efficiency, improves the rate performance and cycle stability, and maintains the structural integrity of the cladding layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004201632450000171
    Figure BDA0004201632450000171
Patent Text Reader

Abstract

The present invention provides a silicon-based composite negative electrode material and a preparation method and application thereof, wherein the silicon-based composite negative electrode material comprises pre-lithiated silicon oxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon oxide particles. In the present invention, there is a strong binding force between the pre-lithiated silicon oxide particles and the ion conductor coating layer, which effectively stabilizes the structure of the material and achieves high-quality coating of the inner core while achieving pre-lithiation. Pre-lithiation of silicon oxide particles not only reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, but also improves its first coulombic efficiency; the high-quality ion conductor coating layer not only promotes Li + The transmission of silicon iodine improves the rate performance of silicon iodine negative electrode materials, and also effectively inhibits the side reactions between active materials and electrolytes, thereby improving the cycle stability of silicon iodine negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a silicon-based composite negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of society and economy, people have put forward higher requirements for the energy density of lithium-ion batteries. Silicon anode based on alloying reaction is considered to be an ideal choice for the next generation of lithium-ion battery anode materials because of its theoretical lithium storage capacity of up to 4200mAh / g. However, in the process of alloying reaction between silicon and lithium, there is a huge volume expansion (>300%), which is prone to deactivation due to particle pulverization, resulting in poor cycle stability. This problem seriously affects the practical application of silicon-based anode.

[0003] Silicon dioxide (chemical formula: SiO x ) negative electrode material, compared with pure silicon negative electrode, has a lower volume expansion rate (~118%), its commercialization is ahead of pure silicon negative electrode, and its application in the power field is more mainstream. During the first charge and discharge process, the silicon oxide negative electrode will react with lithium to generate electrochemically inert lithium oxide (Li2O), lithium silicate (Li2SiO3, Li2Si2O5, etc.) and active nano-silicon clusters. These inert matrices can effectively buffer the volume effect during the alloying and dealloying of nano-silicon clusters and improve the cycle stability of the active components. However, since the formation of lithium oxide and lithium silicate is an irreversible process, the first coulombic efficiency of silicon oxide negative electrode materials is low.

[0004] In response to the above problems, people have developed a variety of pre-lithiation methods. For example, CN114079050A discloses a silicon-oxygen composite material, a preparation method thereof, a negative electrode material and a lithium-ion battery. The silicon-oxygen composite material includes a core and a carbon layer formed on the surface of the core, the core includes a lithium-containing compound and a non-metallic silicon-containing material, the non-metallic silicon-containing material includes at least one of nano-silicon and silicon oxide, and the non-metallic silicon-containing material is dispersed in the lithium-containing compound; the size D10 of the silicon-oxygen composite material is 3.0μm to 8.2μm. CN113948688A discloses a modified pre-lithiation silicon-oxygen composite material, a preparation method thereof and an application in a lithium-ion battery. The modified pre-lithiation silicon-oxygen composite material has a core-shell structure, and comprises, from the inside to the outside, a core of the pre-lithiation silicon-oxygen composite material, a silicon-coated intermediate layer and a carbon layer; the pre-lithiation silicon-oxygen composite material comprises nano-silicon and lithium silicate; the lithium silicate comprises a Li2SiO3 main phase; the content of the silicon-coated intermediate layer is 2 to 93% of the total mass of the core of the pre-lithiation silicon-oxygen composite material and the silicon-coated intermediate layer; the pH value of the modified pre-lithiation silicon-oxygen composite material is 6 to 10. CN112289999A discloses a pre-lithiated silicon oxide / carbon composite material, a preparation method thereof and an application thereof, wherein the preparation method comprises: vapor-depositing a carbon layer on silicon oxide material to prepare a silicon oxide / carbon composite material; crushing the lithium salt to a suitable particle size and then evenly mixing it with silicon oxide / carbon; heating the mixed material to a certain temperature, and keeping it warm for a period of time under a reducing atmosphere to obtain a pre-lithiated silicon oxide / carbon composite material. The above technical scheme pre-forms lithium silicate in the silicon compound through pre-lithiation, thereby reducing the loss of active lithium caused by the first lithium insertion and improving the initial effect. However, the hot doping pre-lithiation method commonly used in industry will destroy the original carbon coating layer on the surface of silicon oxide during the pre-lithiation process, thereby leading to a series of problems such as homogenous gas production and cycle performance degradation.

[0005] Surface coating can not only maintain the structural integrity of the material, but also effectively inhibit side reactions, thereby improving cycle stability. It is an effective solution. Studies have shown that carbon coating has a significant effect on improving the electrochemical performance of silicon-based negative electrode materials. It can not only act as a buffer layer to reduce the volume expansion of silicon-based materials, but also improve the conductivity of composite materials. However, if carbon is coated by thermal chemical vapor deposition after pre-lithiation, the doped lithium will promote the reaction of silicon oxide with the carbon interface layer to produce SiC, and will promote the growth of crystalline silicon, produce large grains, and affect the material performance. In addition, the traditional coating method will cause the coating layer to be uneven, and the bonding force between the coating layer and the base material is weak, which affects the coating effect. In addition, the lithium ion diffusion kinetics of the coating layer also has a great influence on the performance of the silicon-based negative electrode.

[0006] Therefore, achieving high-quality surface coating during pre-lithiation to improve the electrochemical performance of silicon monoxide negative electrode materials is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a silicon-based composite negative electrode material and its preparation method and application. The present invention provides a silicon-based composite negative electrode material with pre-lithiated silicon oxide particles as the core and an ion conductor coating layer as the shell. Pre-lithiating the silicon oxide particles not only reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, but also improves its first coulombic efficiency; the high-quality ion conductor coating layer not only promotes the Li + The transmission of ions improves the rate performance of silicon oxide negative electrode materials, and effectively inhibits the side reactions between active materials and electrolytes, thereby improving the cycle stability of silicon oxide negative electrode materials. In addition, the strong binding force between pre-lithiated silicon oxide particles and the ion conductor coating layer effectively stabilizes the structure of the material, achieving high-quality coating of the core while achieving pre-lithiation, and has good development potential.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a silicon-based composite negative electrode material, comprising pre-lithiated silicon dioxide particles, and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0010] The present invention provides a silicon-based composite negative electrode material with pre-lithiated silicon oxide particles as the core and an ion conductor coating layer as the shell. Pre-lithiating the silicon oxide particles not only reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, but also improves its first coulomb efficiency; the high-quality ion conductor coating layer not only promotes the + The transmission of ions improves the rate performance of silicon oxide negative electrode materials, and effectively inhibits the side reactions between active materials and electrolytes, thereby improving the cycle stability of silicon oxide negative electrode materials. In addition, the strong binding force between pre-lithiated silicon oxide particles and the ion conductor coating layer effectively stabilizes the structure of the material, achieving high-quality coating of the core while achieving pre-lithiation, and has good development potential.

[0011] Preferably, the ion conductor coating comprises lithium orthosilicate.

[0012] Preferably, the thickness of the ion conductor coating layer is 4-10 nm, for example, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0013] In the present invention, if the thickness of the ion conductor coating layer is too thin, the rate performance and cycle performance of the material will not be significantly improved; if the thickness of the ion conductor coating layer is too thick, the capacity of the material will be affected.

[0014] Preferably, based on the mass of the pre-lithiated silicon dioxide particles, the lithium content in the pre-lithiated silicon dioxide particles is 8-10%, for example, 8%, 8.5%, 9%, 9.5% or 10%.

[0015] Preferably, the median particle size of the pre-lithiated silicon monoxide particles is 5-10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0016] In a second aspect, the present invention provides a method for preparing the silicon-based composite negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0017] (1) mixing a silicon oxide material and a silicon source, and performing an in-situ reaction to obtain a silicon dioxide-coated silicon oxide material;

[0018] (2) The silicon dioxide-coated silicon monoxide material and a lithium source are mixed and sintered to obtain the silicon-based composite negative electrode material.

[0019] The present invention uses an in-situ coating-co-lithiation sintering method to pre-lithiate the silicon oxide material while achieving surface coating of the silicon oxide material, so that a strong bonding force is generated between the pre-lithiated silicon oxide material and the coating layer, thereby stabilizing the material structure. This method effectively avoids the damage of the coating layer by pre-lithiation, so that the surface coating layer can maintain structural integrity, effectively inhibit side reactions, and improve the electrochemical performance of the negative electrode material.

[0020] In the present invention, the source of silicon 2 oxide material is not limited, and it can be commercial or homemade.

[0021] Preferably, the silicon source in step (1) comprises any one of tetraethyl silicate, sodium silicate or silicon tetrachloride, or a combination of at least two thereof.

[0022] Preferably, the mass ratio of the silicon dioxide material to the silicon source in step (1) is 50:(1-5), for example, it can be 50:1, 50:1.5, 50:2, 50:2.5, 50:3, 50:3.5, 50:4, 50:4.5 or 50:5, etc.

[0023] In the present invention, if the mass ratio of silicon monoxide material to silicon source is too small, that is, the amount of silicon source used is too much, the coating layer will be too thick, affecting the capacity of the material; if the mass ratio of silicon monoxide material to silicon source is too large, that is, the amount of silicon source used is too small, the coating layer will be too thin, and the rate and cycle performance of the material will not be significantly improved.

[0024] Preferably, the mixing process in step (1) is accompanied by stirring.

[0025] Preferably, the specific steps of mixing in step (1) include:

[0026] (a) dispersing silicon dioxide material in a solvent to obtain a silicon dioxide dispersion;

[0027] (b) dispersing a silicon source in a solvent to obtain a silicon source dispersion;

[0028] (c) mixing the silicon oxide dispersion and the silicon source dispersion, and performing hydrolysis to obtain a hydrolyzed mixture.

[0029] Preferably, the solvent in step (a) comprises any one of water, ethanol, methanol or N-methylpyrrolidone, or a combination of at least two thereof;

[0030] Preferably, the solvent in step (b) comprises any one of water, ethanol, methanol or N-methylpyrrolidone, or a combination of at least two thereof.

[0031] Preferably, the mixing method in step (c) is: adding the silicon source dispersion into the silicon oxide dispersion in a dropwise manner.

[0032] Preferably, aqueous ammonia is added during the hydrolysis process in step (c) to adjust the pH of the hydrolysis environment.

[0033] Preferably, the hydrolysis in step (c) is carried out in a weakly alkaline environment.

[0034] In the present invention, a weakly alkaline environment can catalyze the hydrolysis reaction. If the hydrolysis is carried out in a strongly alkaline environment, the reaction will be accelerated and the particle size will become larger.

[0035] It should be noted that a weakly alkaline environment refers to an environment where the pH value is greater than 7 but close to 7.

[0036] Preferably, the in-situ reaction in step (1) comprises a wet chemical method.

[0037] Preferably, the wet chemical method comprises any one of a chemical precipitation method, a sol-gel method or a microemulsion method.

[0038] Preferably, the in-situ reaction in step (1) includes a primary reaction and a secondary reaction.

[0039] Preferably, the temperature of the primary reaction is 20-40°C, for example, it can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, etc.

[0040] Preferably, the primary reaction time is 4-8 h, for example, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h or 8 h.

[0041] Preferably, the temperature of the secondary reaction is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 46°C, 58°C or 60°C.

[0042] In the present invention, the time of the secondary reaction is not limited, and the solvent can be completely evaporated.

[0043] Preferably, the lithium source in step (2) includes any one of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium hydride, lithium nitride or lithium element, or a combination of at least two thereof.

[0044] Preferably, the mass ratio of the silica-coated silicon dioxide material to the lithium source in step (2) is 20:(10-15), for example, it can be 20:10, 20:11, 20:12, 20:13, 20:14 or 20:15, etc.

[0045] In the present invention, if the mass ratio of the silicon dioxide-coated silicon oxide material to the lithium source is too small, that is, the amount of lithium source is too much, the pre-lithiation is excessive, and Li4SiO4 and Li x Si, and resulting in poor material processing performance; if the mass ratio of the silicon dioxide-coated silicon oxide material and the lithium source is too large, that is, the amount of lithium source is too small, it will lead to insufficient pre-lithium and a low initial efficiency of the material.

[0046] Preferably, the sintering atmosphere in step (2) is an inert atmosphere or a vacuum atmosphere.

[0047] Preferably, the gas in the inert atmosphere includes argon and / or nitrogen.

[0048] Preferably, the sintering temperature in step (2) is 700-900°C, for example, it can be 700°C, 750°C, 800°C, 850°C or 900°C.

[0049] In the present invention, if the sintering temperature in step (2) is too low, the pre-lithium is incomplete, the first effect is low, and the residual alkali is too high, affecting the processability; if the sintering temperature in step (2) is too high, silicon dioxide undergoes a disproportionation reaction, resulting in an excessively large Si grain size, affecting the material's cycle performance.

[0050] Preferably, the sintering time in step (2) is 3-7 h, for example, it can be 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h or 7 h.

[0051] As a preferred technical solution, the preparation method comprises the following steps:

[0052] (1) Preparation of silicon dioxide-coated silicon dioxide material by wet chemical method:

[0053] Mixing a silicon oxide material and a silicon source in a mass ratio of 50:(1-5), and then performing a primary reaction at 20-40° C. for 4-8 hours, and performing a secondary reaction at 40-60° C. until the solvent is completely evaporated, to obtain a silicon dioxide-coated silicon oxide material;

[0054] (2) Under stirring conditions, the silicon dioxide-coated silicon dioxide material and a lithium source are mixed in a mass ratio of 20:(10-15), and sintered at 700-900° C. for 3-7 hours in an inert atmosphere to obtain the silicon-based composite negative electrode material.

[0055] In a third aspect, the present invention provides a lithium-ion battery, wherein the negative electrode of the lithium-ion battery comprises the silicon-based composite negative electrode material as described in the first aspect.

[0056] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The present invention provides a silicon-based composite negative electrode material with pre-lithiated silicon oxide particles as the core and an ion conductor coating layer as the shell. Pre-lithiating the silicon oxide particles not only reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, but also improves its first coulombic efficiency; the high-quality ion conductor coating layer not only promotes the Li + The transmission of ions improves the rate performance of silicon dioxide anode materials, and also effectively inhibits the side reactions between active materials and electrolytes, thereby improving the cycle stability of silicon dioxide anode materials;

[0059] (2) The present invention uses an in-situ coating-co-lithiation sintering method to pre-lithiate the silicon oxide material while achieving in-situ coating on the surface of the silicon oxide material, so that a strong bonding force is generated between the pre-lithiated silicon oxide material and the coating layer, thereby stabilizing the material structure. This method effectively avoids the damage of the coating layer by pre-lithiation, so that the surface coating layer can maintain structural integrity, effectively inhibit side reactions, and improve the electrochemical performance of the negative electrode material;

[0060] (3) The capacity of the silicon-based composite negative electrode material provided by the present invention is between 1300-1500 mAh / g, the first efficiency is between 88-92%, and it has excellent electrochemical performance. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a silicon-based composite negative electrode material, which includes pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0064] The ion conductor coating layer is a lithium orthosilicate coating layer with a thickness of 6.4 nm; based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 9.1%; and the median particle size of the pre-lithiated silicon oxide particles is 5.6 μm.

[0065] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, the preparation method comprising the following steps:

[0066] (1) 50 g of commercial silicon dioxide material was dispersed in 500 mL of ethanol-water solution (volume ratio of ethanol to water = 1:2), and then stirred on a magnetic stirrer after ultrasonic treatment for 5 min to obtain a silicon dioxide dispersion; 2 g of tetraethyl silicate was added to 10 mL of anhydrous ethanol, and stirred to mix evenly to obtain a tetraethyl silicate dispersion;

[0067] Wherein, the mass ratio of silicon oxide material to tetraethyl silicate is 50:2;

[0068] (2) Preparation of silicon dioxide-coated silicon dioxide material by chemical precipitation method:

[0069] The tetraethyl silicate dispersion was added dropwise to the silicon oxide dispersion under stirring conditions, and after continuing to stir and disperse for 30 minutes, 2 mL of ammonia water (mass fraction of 28 wt.%) was slowly added thereto to hydrolyze the tetraethyl silicate under weak alkaline conditions to obtain SiO2; the obtained mixture was then subjected to a primary reaction under stirring conditions for 6 hours at a temperature of 30°C, and then a secondary reaction was carried out at 50°C, and stirred until the solvent was completely evaporated to obtain a silicon dioxide-coated silicon oxide material, recorded as SiO2. x @SiO2;

[0070] (3) 20 g of the SiO x@SiO2 and 11.8g of lithium hydroxide monohydrate were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 800℃ for 5h under argon atmosphere to obtain a lithium orthosilicate-coated pre-lithiated silicon oxide negative electrode material, denoted as Li-SiO x @Li4SiO4;

[0071] Among them, SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:11.8.

[0072] Example 2

[0073] This embodiment provides a silicon-based composite negative electrode material, which includes pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0074] The ion conductor coating layer is a lithium orthosilicate coating layer with a thickness of 8.9 nm; based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 9.3%; and the median particle size of the pre-lithiated silicon oxide particles is 6.5 μm.

[0075] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, the preparation method comprising the following steps:

[0076] (1) 50 g of commercial silicon dioxide material was dispersed in 500 mL of ethanol-water solution (volume ratio of ethanol to water = 1:2), and then stirred on a magnetic stirrer after ultrasonic treatment for 5 min to obtain a silicon dioxide dispersion; 4 g of tetraethyl silicate was added to 10 mL of anhydrous ethanol, and stirred to mix evenly to obtain a tetraethyl silicate dispersion;

[0077] Wherein, the mass ratio of silicon dioxide material to tetraethyl silicate is 50:4;

[0078] (2) Preparation of silicon dioxide-coated silicon dioxide material by chemical precipitation method:

[0079] The tetraethyl silicate dispersion was added dropwise to the silicon oxide dispersion under stirring conditions, and after continuing to stir and disperse for 30 minutes, 2 mL of ammonia water (mass fraction of 28 wt.%) was slowly added thereto to hydrolyze the tetraethyl silicate under weak alkaline conditions to obtain SiO2; the obtained mixture was then subjected to a primary reaction under stirring conditions for 6 hours at a temperature of 30°C, and then a secondary reaction was carried out at 50°C, and stirred until the solvent was completely evaporated to obtain a silicon dioxide-coated silicon oxide material, recorded as SiO2. x @SiO2;

[0080] (3) 20 g of the SiO x@SiO2 and 11.8g of lithium hydroxide monohydrate were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 800℃ for 5h under argon atmosphere to obtain a lithium orthosilicate-coated pre-lithiated silicon oxide negative electrode material, denoted as Li-SiO x @Li4SiO4;

[0081] Among them, SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:11.8.

[0082] Example 3

[0083] This embodiment provides a silicon-based composite negative electrode material, which includes pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0084] The ion conductor coating layer is a lithium orthosilicate coating layer with a thickness of 4.6 nm; based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 8.8%; and the median particle size of the pre-lithiated silicon oxide particles is 6.2 μm.

[0085] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, the preparation method comprising the following steps:

[0086] (1) 50 g of commercial silicon dioxide material was dispersed in 500 mL of ethanol-water solution (volume ratio of ethanol to water = 1:2), and then stirred on a magnetic stirrer after ultrasonic treatment for 5 min to obtain a silicon dioxide dispersion; 1 g of tetraethyl silicate was added to 10 mL of anhydrous ethanol, and stirred to mix evenly to obtain a tetraethyl silicate dispersion;

[0087] Wherein, the mass ratio of silicon dioxide material to tetraethyl silicate is 50:1;

[0088] (2) Preparation of silicon dioxide-coated silicon dioxide material by chemical precipitation method:

[0089] The tetraethyl silicate dispersion was added dropwise to the silicon oxide dispersion under stirring conditions, and after continuing to stir and disperse for 30 minutes, 2 mL of ammonia water (mass fraction of 28 wt.%) was slowly added thereto to hydrolyze the tetraethyl silicate under weak alkaline conditions to obtain SiO2; the obtained mixture was then subjected to a primary reaction under stirring conditions for 6 hours at a temperature of 30°C, and then a secondary reaction was carried out at 50°C, and stirred until the solvent was completely evaporated to obtain a silicon dioxide-coated silicon oxide material, recorded as SiO2. x @SiO2;

[0090] (3) 20 g of the SiO x@SiO2 and 11.8g of lithium hydroxide monohydrate were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 800℃ for 5h under argon atmosphere to obtain a lithium orthosilicate-coated pre-lithiated silicon oxide negative electrode material, denoted as Li-SiO x @Li4SiO4;

[0091] Among them, SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:11.8.

[0092] Example 4

[0093] This embodiment provides a silicon-based composite negative electrode material, which includes pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0094] The ion conductor coating layer is a lithium orthosilicate coating layer with a thickness of 6.8 nm. Based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 9.3%. The median particle size of the pre-lithiated silicon oxide particles is 7.2 μm.

[0095] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, the preparation method comprising the following steps:

[0096] (1) 50 g of commercial silicon dioxide material was dispersed in 500 mL of ethanol-water solution (volume ratio of ethanol to water = 1:2), and then stirred on a magnetic stirrer after ultrasonic treatment for 5 min to obtain a silicon dioxide dispersion; 3 g of tetraethyl silicate was added to 10 mL of anhydrous ethanol, and stirred to mix evenly to obtain a tetraethyl silicate dispersion;

[0097] Wherein, the mass ratio of silicon dioxide material to tetraethyl silicate is 50:3;

[0098] (2) Preparation of silicon dioxide-coated silicon dioxide material by chemical precipitation method:

[0099] The tetraethyl silicate dispersion was added dropwise to the silicon oxide dispersion under stirring conditions. After continuing to stir and disperse for 30 minutes, 2 mL of ammonia water (mass fraction of 28 wt.%) was slowly added thereto to hydrolyze the tetraethyl silicate under weak alkaline conditions to obtain SiO2. The obtained mixture was then subjected to a primary reaction under stirring conditions for 4 hours at a temperature of 40°C, and then a secondary reaction was carried out at 40°C, and stirred until the solvent was completely evaporated to obtain a silicon dioxide-coated silicon oxide material, which was recorded as SiO2. x @SiO2;

[0100] (3) 20 g of the SiO x@SiO2 and 14g of lithium hydroxide monohydrate were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 700℃ for 9h under argon atmosphere to obtain a lithium orthosilicate-coated pre-lithiated silicon dioxide anode material, denoted as Li-SiO x @Li4SiO4;

[0101] Among them, SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:14.

[0102] Example 5

[0103] This embodiment provides a silicon-based composite negative electrode material, which includes pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles.

[0104] The ion conductor coating layer is a lithium orthosilicate coating layer with a thickness of 4.3 nm; based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 9.5%; and the median particle size of the pre-lithiated silicon oxide particles is 6.8 μm.

[0105] This embodiment also provides a method for preparing a silicon-based composite negative electrode material, the preparation method comprising the following steps:

[0106] (1) 50 g of commercial silicon dioxide material was dispersed in 500 mL of ethanol-water solution (volume ratio of ethanol to water = 1:2), and then stirred on a magnetic stirrer after ultrasonic treatment for 5 minutes to obtain a silicon dioxide dispersion; 5 g of tetraethyl silicate was added to 10 mL of anhydrous ethanol, and stirred to mix evenly to obtain a tetraethyl silicate dispersion;

[0107] Wherein, the mass ratio of silicon oxide material to tetraethyl silicate is 50:5;

[0108] (2) Preparation of silicon dioxide-coated silicon dioxide material by chemical precipitation method:

[0109] The tetraethyl silicate dispersion was added dropwise to the silicon oxide dispersion under stirring conditions, and after continuing to stir and disperse for 30 minutes, 2 mL of ammonia water (mass fraction of 28 wt.%) was slowly added thereto to hydrolyze the tetraethyl silicate under weak alkaline conditions to obtain SiO2; the obtained mixture was then subjected to a primary reaction under stirring conditions for 8 hours at a temperature of 20°C, and then a secondary reaction was carried out at 60°C, and stirred until the solvent was completely evaporated to obtain a silicon dioxide-coated silicon oxide material, recorded as SiO2. x @SiO2;

[0110] (3) 20 g of the SiO x@SiO2 and 14g of lithium hydride were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 900℃ for 3h under argon atmosphere to obtain a lithium orthosilicate-coated pre-lithiated silicon dioxide anode material, denoted as Li-SiO x @Li4SiO4;

[0111] Among them, SiO x @The mass ratio of SiO2 and lithium hydride is 20:14.

[0112] Example 6

[0113] The difference between this embodiment and embodiment 1 is that the mass ratio of silicon dioxide material to tetraethyl silicate is 50:0.5.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Example 7

[0116] The difference between this embodiment and embodiment 1 is that the mass ratio of silicon dioxide material to tetraethyl silicate is 50:6.

[0117] The rest of the preparation methods and parameters were the same as those in Example 1.

[0118] Example 8

[0119] The difference between this embodiment and embodiment 1 is that the 2 mL of aqueous ammonia in step (2) is replaced by 10 mL of aqueous ammonia, so that tetraethyl silicate is hydrolyzed under strong alkaline conditions.

[0120] The rest of the preparation methods and parameters were the same as those in Example 1.

[0121] Example 9

[0122] The difference between this embodiment and embodiment 1 is that SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:20.

[0123] The rest of the preparation methods and parameters were the same as those in Example 1.

[0124] Example 10

[0125] The difference between this embodiment and embodiment 1 is that SiO x @The mass ratio of SiO2 and lithium hydroxide monohydrate is 20:5.

[0126] The rest of the preparation methods and parameters were the same as those in Example 1.

[0127] Embodiment 11

[0128] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (3) is 600°C.

[0129] The rest of the preparation methods and parameters were the same as those in Example 1.

[0130] Example 12

[0131] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (3) is 1000°C.

[0132] The rest of the preparation methods and parameters were the same as those in Example 1.

[0133] Comparative Example 1

[0134] The difference between this comparative example and Example 1 is that steps (1) to (3) are not performed, that is, only commercial silicon dioxide material is used as the negative electrode material.

[0135] Comparative Example 2

[0136] This comparative example provides a silicon-based composite negative electrode material, wherein the silicon-based composite negative electrode material is a pre-lithiated silicon oxide negative electrode material, and the preparation method of the pre-lithiated silicon oxide negative electrode material comprises the following steps:

[0137] 20 g of commercial silicon dioxide anode material and 11.73 g of lithium hydroxide monohydrate were ground and mixed in an agate mortar, and then placed in a tube furnace and sintered at 800 °C for 5 h under argon atmosphere to obtain a pre-lithiated silicon dioxide anode material, denoted as Li-SiO x .

[0138] Performance Testing

[0139] (I) Power-off test

[0140] The silicon-based composite negative electrode materials provided in Examples 1-12 and Comparative Examples 1-2 were used as active materials and the electrochemical performance of Xining was tested and analyzed. The specific steps included:

[0141] ① Preparation of negative electrode sheet: Active material, carbon black and polyacrylic acid (PAA) were mixed in a weight ratio of 8:1:1 and dispersed in deionized water to form a uniform slurry. The slurry was then cast on copper foil by a doctor blade method and vacuum dried at 60°C for 12 hours;

[0142] ② Assemble 2016-type button cells in a glove box filled with inert gas, in which the contents of H2O and O2 were both less than 0.1 ppm; use metal lithium sheets as counter electrodes, and adopt 1M LiPF6 (EC:EMC:DMC=1vol%:1vol%:1vol%) + 3%FEC as electrolyte and PP separator; use LAND CT2001A battery testing system to perform constant current charge / discharge tests at room temperature, and the test procedure is: 0.1C discharge to 5 mV, 0.05C discharge to 5 mV, 0.02C discharge to 5 mV, 0.01C discharge to 5 mV, and then 0.1C charge to 1.5 V.

[0143] (II) Cycle test

[0144] The silicon-based composite negative electrode material provided in Example 1-12 and Comparative Example 1-2 and graphite were mixed uniformly in a mass ratio of 1:9 and then used as an active material for electrochemical performance testing and analysis. The specific steps include:

[0145] ① Preparation of negative electrode sheet: Active material, carbon black and polyacrylic acid (PAA) were mixed in a weight ratio of 90:5:5 and dispersed in deionized water to form a uniform slurry. The slurry was then cast on copper foil by a doctor blade method and vacuum dried at 60°C for 12 hours;

[0146] ② Assemble 2016-type button cells in a glove box filled with inert gas, in which the contents of H2O and O2 were both less than 0.1 ppm; use metal lithium sheets as counter electrodes, and adopt 1M LiPF6 (EC:EMC:DMC=1vol%:1vol%:1vol%) + 3% FEC as electrolyte and PP separator; use LAND CT2001A battery testing system to perform constant current charge / discharge cycle tests at room temperature, with a charge and discharge rate of 0.1C and a voltage window of 0.01-2V.

[0147] (III) Rate performance

[0148] The silicon-based composite negative electrode material provided in Example 1-12 and Comparative Example 1-2 and graphite were mixed uniformly in a mass ratio of 1:9 and then used as an active material for electrochemical performance testing and analysis. The specific steps include:

[0149] ① Preparation of negative electrode sheet: Active material, carbon black and polyacrylic acid (PAA) were mixed in a weight ratio of 90:5:5 and dispersed in deionized water to form a uniform slurry. The slurry was then cast on copper foil by a doctor blade method and vacuum dried at 60°C for 12 hours;

[0150] ② Assemble 2016-type button cells in a glove box filled with inert gas, in which the contents of H2O and O2 are both lower than 0.1ppm; use metal lithium sheets as counter electrodes, and adopt 1M LiPF6 (EC:EMC:DMC=1vol%:1vol%:1vol%)+3%FEC as electrolyte and PP separator; use LAND CT2001A battery testing system to carry out rate performance test at room temperature, and the test steps are as follows: 1) first discharge at 0.5C to 5mV, discharge at 0.05C to 5mV, discharge at 0.02C to 5mV, discharge at 0.01C to 5mV, and then charge at 0.1C to 2V; 2) keep the discharge procedure unchanged, and charge at 0.2C to 2V; 3) keep the discharge procedure unchanged, and charge at 0.5C to 2V; 4) keep the discharge procedure unchanged, and charge at 1C to 2V.

[0151] The above test results are shown in Table 1.

[0152] Table 1

[0153]

[0154] analyze:

[0155] As can be seen from the above table, the silicon-based composite negative electrode material prepared by the present invention achieves high-quality coating of the core while achieving pre-lithiation, which not only reduces the irreversible capacity of the silicon oxide negative electrode in the first cycle, but also improves its first coulombic efficiency. In addition, the rate performance and cycle stability of the silicon oxide negative electrode material are effectively improved.

[0156] By comparing the data results of Example 1 with those of Examples 6-7, it can be seen that if the mass ratio of silicon monoxide material to silicon source is too small, that is, the amount of silicon source used is too much, the coating layer will be too thick, resulting in the capacity of the material being too low; if the mass ratio of silicon monoxide material to silicon source is too small, that is, the amount of silicon source used is too much, the coating layer will be too thin, resulting in no obvious improvement in the rate and cycle performance of the material.

[0157] From the comparison of the data results of Example 1 and Example 8, it can be seen that if tetraethyl silicate is hydrolyzed under strong alkaline conditions, the reaction will be accelerated and the particle size will become larger, thereby resulting in an uneven coating layer and poor performance.

[0158] By comparing the data results of Example 1 with those of Examples 9-10, it can be seen that if the mass ratio of the silica-coated silicon dioxide oxide material and the lithium source is too small, that is, the amount of lithium source used is too much, excessive pre-lithiation will occur to form Li4SiO4 and LixSi, and the material processing performance will be poor, resulting in poor overall performance; if the mass ratio of the silica-coated silicon dioxide oxide material and the lithium source is too large, that is, the amount of lithium source used is too small, insufficient pre-lithiation will result, resulting in a lower initial efficiency of the material.

[0159] By comparing the data results of Example 1 with those of Examples 11-12, it can be seen that if the sintering temperature is too low, the pre-lithium will be incomplete, resulting in a low first effect and too high residual alkali, affecting the processability; if the sintering temperature is too high, silicon dioxide will undergo a disproportionation reaction, resulting in the Si grain size being too large, affecting the material's cycle performance.

[0160] From the comparison of the data results of Example 1 and Comparative Example 1, it can be seen that if only commercial silicon dioxide material is used as the negative electrode material, the overall performance is poor.

[0161] From the comparison of the data results of Example 1 and Comparative Example 2, it can be seen that if only silicon oxide is pre-lithiated, the cycle and rate performance are poor.

[0162] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A silicon-based composite negative electrode material, characterized in that: The silicon-based composite negative electrode material is composed of pre-lithiated silicon dioxide particles and an ion conductor coating layer located on the surface of the pre-lithiated silicon dioxide particles; The ion conductor coating layer is lithium orthosilicate; The silicon-based composite negative electrode material is prepared by the following method, which comprises the following steps: (1) mixing a silicon oxide material and a silicon source, and performing an in-situ reaction to obtain a silicon dioxide-coated silicon oxide material; The mass ratio of the silicon dioxide material to the silicon source in step (1) is 50:(1-5); The specific steps of mixing in step (1) include: (a) dispersing silicon dioxide material in a solvent to obtain a silicon dioxide dispersion; (b) dispersing a silicon source in a solvent to obtain a silicon source dispersion; (c) mixing the silicon oxide dispersion and the silicon source dispersion, and performing hydrolysis to obtain a hydrolyzed mixture; The hydrolysis in step (c) is carried out in a weakly alkaline environment; (2) mixing the silicon dioxide-coated silicon dioxide material and a lithium source, and sintering to obtain the silicon-based composite negative electrode material; In step (2), the mass ratio of the silicon dioxide-coated silicon monoxide material to the lithium source is 20:(10-15).

2. The silicon-based composite negative electrode material according to claim 1, characterized in that: The thickness of the ion conductor coating layer is 4-10 nm.

3. The silicon-based composite negative electrode material according to claim 1, characterized in that: Based on the mass of the pre-lithiated silicon oxide particles, the lithium content in the pre-lithiated silicon oxide particles is 8-10%.

4. The silicon-based composite negative electrode material according to claim 1, characterized in that: The median particle size of the pre-lithiated silicon dioxide particles is 5-10 μm.

5. A method for preparing a silicon-based composite negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a silicon oxide material and a silicon source, and performing an in-situ reaction to obtain a silicon dioxide-coated silicon oxide material; The mass ratio of the silicon dioxide material to the silicon source in step (1) is 50:(1-5); The specific steps of mixing in step (1) include: (a) dispersing silicon dioxide material in a solvent to obtain a silicon dioxide dispersion; (b) dispersing a silicon source in a solvent to obtain a silicon source dispersion; (c) mixing the silicon oxide dispersion and the silicon source dispersion, and hydrolyzing them to obtain a hydrolyzed mixture; The hydrolysis in step (c) is carried out in a weakly alkaline environment; (2) mixing the silicon dioxide-coated silicon dioxide material and a lithium source, and sintering to obtain the silicon-based composite negative electrode material; In step (2), the mass ratio of the silicon dioxide-coated silicon dioxide material to the lithium source is 20:(10-15).

6. The preparation method according to claim 5, characterized in that: The silicon source in step (1) includes any one of tetraethyl silicate, sodium silicate or silicon tetrachloride, or a combination of at least two of them.

7. The preparation method according to claim 5, characterized in that: The in-situ reaction method of step (1) includes wet chemical method.

8. The preparation method according to claim 7, characterized in that: The wet chemical method includes any one of a chemical precipitation method, a sol-gel method or a microemulsion method.

9. The preparation method according to claim 5, characterized in that: The in-situ reaction in step (1) includes a primary reaction and a secondary reaction.

10. The preparation method according to claim 9, characterized in that: The temperature of the primary reaction is 20-40°C.

11. The preparation method according to claim 9, characterized in that: The time of the primary reaction is 4-8h.

12. The preparation method according to claim 9, characterized in that: The temperature of the secondary reaction is 40-60°C.

13. The preparation method according to claim 5, characterized in that: The lithium source in step (2) includes any one of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium hydride, lithium nitride or lithium element or a combination of at least two thereof.

14. The preparation method according to claim 5, characterized in that: The sintering atmosphere in step (2) is an inert atmosphere or a vacuum atmosphere.

15. The preparation method according to claim 14, characterized in that: The gas in the inert atmosphere includes argon and / or nitrogen.

16. The preparation method according to claim 5, characterized in that: The sintering temperature in step (2) is 700-900°C.

17. The preparation method according to claim 5, characterized in that: The sintering time in step (2) is 3-7 hours.

18. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: (1) Preparation of silicon dioxide-coated silicon dioxide material by wet chemical method: Mixing a silicon oxide material and a silicon source in a mass ratio of 50:(1-5), and then performing a primary reaction at 20-40° C. for 4-8 hours, and performing a secondary reaction at 40-60° C. until the solvent is completely evaporated, to obtain a silicon dioxide-coated silicon oxide material; The specific steps of the mixing include: (a) dispersing silicon dioxide material in a solvent to obtain a silicon dioxide dispersion; (b) dispersing a silicon source in a solvent to obtain a silicon source dispersion; (c) mixing the silicon oxide dispersion and the silicon source dispersion, and hydrolyzing them to obtain a hydrolyzed mixture; The hydrolysis in step (c) is carried out in a weakly alkaline environment; (2) Under stirring conditions, the silicon dioxide-coated silicon dioxide material and a lithium source are mixed in a mass ratio of 20:(10-15), and sintered at 700-900° C. for 3-7 hours in an inert atmosphere to obtain the silicon-based composite negative electrode material.

19. A lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery comprises the silicon-based composite negative electrode material as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Pre-lithiated silicon monoxide / carbon composite material, and preparation method and application thereof

    CN112289999A

  • Modified pre-lithiated silica composite material as well as preparation method and application thereof

    CN113948688A

  • Silicon-oxygen composite material, preparation method thereof, negative electrode material and lithium ion battery

    CN114079050A

  • Solid electrolyte coated silicon-based negative electrode material and preparation method thereof

    CN110071280A

  • Silicon-oxygen composite negative electrode material, preparation method thereof and lithium ion battery

    CN111710845A